Menggali Makna Wirid Setelah Sholat dengan Bahasa Medis - Abdurrasyid, Muhsin; Bilqis, Nisrina Qothrun Nada; Anindya, Rahmanida Salwa; Amiruddin, Muhammad (Maliki Interdisciplinary Journal, 2025)
Wirid is a recitation of prayers, dhikr, or verses from the Quran that are recited routinely and repeatedly at specific times, usually after the obligatory prayers or in the morning and evening. Recitations of wirid include repeated istighfar (recitation of prayer), tasbih (prayer beads), tahmid (recitation of prayer), takbir (recitation of prayer), and prayers. Besides being a form of worship, wirid also serves as a means of developing the character of patience, sincerity, and positive thinking. Wirid also reduces stress levels, calms the nervous system, and increases inner and emotional calm. Integrating wirid into community health services has the potential to be an effective holistic strategy because it aligns with the religious and cultural values ​​of the community. However, further research is needed to ensure its scientific validity and long-term effectiveness in supporting physical, psychological, social, and spiritual well-being in an integrated manner.